AN ANALYSIS OF IDEOLOGIES IN FAKE NEWS ABOUT THE HISTORY AND USE OF THE CHLOROQUINE IN THE COVID-19 PANDEMIC (PERcursos Linguísticos, 2023)
Deleuze (1990/1992) proposes that the societies of control perform ways of vigilance and authority by modulations. Consequently, any space would be subject of these means of control. For this reason, the objective of this article is to analyze ideologies present in fake news about the history and use of the chloroquine in the context of the Covid-19 pandemic through the deleuzian vision of the societies of control, by setting them in discourses spread through social medias and their algorithms. Consequently, a historical review about fake news and social media was necessary. The website for the Brazilian fact-checking and combating misinformation platform, Agência Lupa, was used as a way of generating the data from the present article. The methodology applied here consists in the qualitative analysis of fake news taken from fact-checks of the website by using two main theoretical and analytical constructs: the chronotope (Blommaert, 2015) and the indexicality (Silverstein, 2006). With this in mind, this article proposes to analyze how some signs – being them linguistic or not – evoke different times and spaces, connecting discourses and ideologies in favor of the view of government of the then-President of Brazil, especially when some discourses were against his idea of government.
Keywords: Fake News; Chloroquine; Covid-19; Ideologies; Indexicality